Adsorption of BTX Aromatic from Reformate by 13X Molecular Sieve - A.K. Mohammed, Abdul Halim; Mehdi Abdul-Raheem, Maisa (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
This work deals with separation of the aromatic hydrocarbons benzene, toluene, and xylene (BTX) from reformate. The separation was examined using adsorption by molecular sieve zeolite 13X in a fixed bed process. The concentration of aromatic hydrocarbons in the influent and effluent streams was measured using gas chromatography. The effect of flow rate and bed length of adsorbent on the adsorption of multicomponent hydrocarbons and adsorption capacity of molecular sieve was studied. The tendency of aromatic hydrocarbons adsorption from reformate is in the order: benzene >toluene>xylenes.